2021
DOI: 10.31083/j.jin2002027
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E ε4 and ε3 alleles associate with cerebrospinal fluid tau and cognition in the presence of amyloid-𝜷 in mild cognitive impairment but not in Alzheimer’s disease

Abstract: Apolipoprotein E is the most well-established genetic risk factor for Alzheimer's disease. However, the associations of apolipoprotein E with tau pathology and cognition remain controversial. The research checks the hypothesis that the relationships between apolipoprotein E alleles and cerebrospinal fluid tau and cognition differ in persons with and without significant amyloid-β deposition. We divided 1119 subjects into cognitively normal (n = 275), mild cognitive impairment (n = 629), and Alzheimer's disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…GPX4 inhibits lipid peroxidation by directly reducing hydroperoxides in membrane lipids [ 80 ], exhibiting direct detoxification. Wang et al [ 68 ]found that in mice with repetitive mild traumatic brain injury (RmTBI), GPX inactivation, decrease in GPX4 levels, increase in lipid peroxidation, abnormal iron metabolism, and mitochondrial ultrastructural changes, are key risk factors for neurodegeneration, characterized by increased deposition of Aβ and tau proteins and cognitive impairment [ 81 ]. By reducing pathological protein deposition after RmTBI and promoting glucose metabolism, MSCs can alleviate neuronal degeneration, effectively regulate protein levels related to iron metabolism, inhibit iron accumulation, reduce RmTBI-induced Fer2+ accumulation, regulate iron metabolism, prevent lipid peroxidation by restoring GPX activity and GPX4 content, and inhibit ferroptosis ( Fig.…”
Section: Application Of Mscsmentioning
confidence: 99%
“…GPX4 inhibits lipid peroxidation by directly reducing hydroperoxides in membrane lipids [ 80 ], exhibiting direct detoxification. Wang et al [ 68 ]found that in mice with repetitive mild traumatic brain injury (RmTBI), GPX inactivation, decrease in GPX4 levels, increase in lipid peroxidation, abnormal iron metabolism, and mitochondrial ultrastructural changes, are key risk factors for neurodegeneration, characterized by increased deposition of Aβ and tau proteins and cognitive impairment [ 81 ]. By reducing pathological protein deposition after RmTBI and promoting glucose metabolism, MSCs can alleviate neuronal degeneration, effectively regulate protein levels related to iron metabolism, inhibit iron accumulation, reduce RmTBI-induced Fer2+ accumulation, regulate iron metabolism, prevent lipid peroxidation by restoring GPX activity and GPX4 content, and inhibit ferroptosis ( Fig.…”
Section: Application Of Mscsmentioning
confidence: 99%
“…In addition, the APOE genotype is also one influencing factor for cognitive decline. Both APOE ε3 and APOE ε4 have impact on cognition of MCI, with APOE ε4 having a more obvious negative effect, the APOE ε3 is also related to cognitive impairment for MCI with Aβ deposition (Xing et al, 2021). Ho and Yang reported a correlation between high Clinical Dementia Rating Sum of Boxes (CDR‐SOB) scores and Aβ‐PET (+) in patients with APOE ε3/ε3 MCI (Ho & Yang, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…closely related to genetics, aging, lifestyle, environmental factors, and nervous system diseases [1][2][3][4], but so far, the etiology and pathogenesis of AD is not clear. Although researchers have proposed the hypothesis of amyloid-␤ (A␤) cascade damage [5], tau hyperphosphorylation [5], cholinergic injury hypothesis [6], the ApoE hypothesis [7], neuroinflammatory hypothesis [8], and mitochondrial dysfunction hypothesis [9] for AD, they have yet to fully explain the complex mechanism of this disease. The prevalence of AD continues to rise, seriously affecting healthcare systems worldwide [10].…”
Section: Introductionmentioning
confidence: 99%